2016
DOI: 10.19030/jber.v14i1.9554
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and the Fear of Missing Out: Scale Development and Assessment

Abstract: For many, viewing social media causes them to relate their own lives to what they are seeing or reading, resulting in feelings that they are somehow missing out.  It is suggested that the fear of missing out influences decision making and behavior. The current research explores the measurement of FOMO, focusing on scale development and validation. Using extant scales for inadequacy, irritability, anxiety, and self- esteem, a list of items (n=37), postulated to measure FOMO, was created. In addition to the scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
250
3
41

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(300 citation statements)
references
References 25 publications
(16 reference statements)
6
250
3
41
Order By: Relevance
“…concept, 70% of the adult millennials (18-34 year olds) indicated that they were completely or somewhat associated with this concept (Abel et al, 2016). According to Hayran et al (2017Hayran et al ( , 2016, 81% of 936 participants stated that they experienced fomo at least occasionally or more frequently; this result and similar results support that fomo is a common phenomenon.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…concept, 70% of the adult millennials (18-34 year olds) indicated that they were completely or somewhat associated with this concept (Abel et al, 2016). According to Hayran et al (2017Hayran et al ( , 2016, 81% of 936 participants stated that they experienced fomo at least occasionally or more frequently; this result and similar results support that fomo is a common phenomenon.…”
Section: Introductionmentioning
confidence: 80%
“…Previous research on fomo has examined several aspects of the issue in terms of an emotional experience felt by individuals (McDermott, 2017), the relationship between fomo and personality or self and the assessment that have been indicated life satisfaction to address the phenomenon. Additionally, a considerable amount of the past research surrounding fomo has focused on multiple identities (Larkin, & Fink, 2016), social media involvement, anxiety, and feelings of inadequacy (Abel, Buff, & Burr, 2016). The symbiotic relationship between fomo and consumption is a fundamental part of social media marketing studies.…”
Section: Fomo-based Consumption or Vice Versamentioning
confidence: 99%
“…El comportamiento adictivo se caracteriza por la pérdida de control generando en la persona consecuencias en su entorno familiar, académico y social (Becoña y Cortés, 2011). En este contexto, los adolescentes y jóvenes representan una población vulnerable debido a que usan esta plataforma como una herramienta interactiva para el desarrollo de diversas actividades (como es el caso de escolares y universitarios), sin embargo la continua actualización de noticias, el incremento de usuarios, las conversaciones espontáneas con sus pares y diversos estímulos distractores son variables que mantienen el uso frecuente a esta RSV que contribuye al proceso adictivo y por ende consecuencias negativas en el repertorio conductual caracterizado por la relevancia, tolerancia, cambios en el estado de ánimo, síntomas de abstinencia, presencia de conflictos ocasionado por el uso intensivo y recaídas (Andreassen, 2015;Hormes, Kears y Timko, 2014 (Abel, Buff, y Burr, 2016). El FoMO es un factor potenciador que impulsa la conducta de conexión (uso y abuso) al aumentar la participación en las redes sociales, especialmente en el grupo de los jóvenes que constantemente actualizan sus RSV y retroalimentan a sus pares siguiendo un ciclo de conexión (Abel et al, 2016;Alt, 2015).…”
Section: Abstract: Addiction Measurement Equivalence Facebook Reliunclassified
“…Fear of Missing Out is defined as the feeling of discomfort or even the feeling of loss that results from knowing what one's friends are doing, and feeling that those friends have it better than them (Abel, Buff, & Burr, 2016 The higher an individual's Fear of Missing Out, the more immersed the individual will be in social media activities, including in online self-presentation (Alt, 2015). Social media makes individuals present themselves online, build communications, as well as December 2017 | Vol.…”
Section: Makara Hubs-asiamentioning
confidence: 99%
“…Fear of Missing Out is a feeling of discomfort which makes an individual feel left out, with the knowledge that their friends have something that the individual does not, or that their friends have something more meaningful than them (Abel et al, 2016).…”
Section: Fear Of Missing Out (Fomo)mentioning
confidence: 99%